APPLICATION OF THE WEIGHTED PRODUCT (WP) ALGORITHM FOR DETERMINING PRIORITY LOCATIONS FOR FAMILY PLANNING PROGRAM EXTENSIONS IN TANJUNGBALAI CITY - Herry herry; Hambali Hambali; Sri Rezki Maulina Azmi (Jurnal Ipteks Terapan (Research Of Applied Science And Education ), 2022)
Family Planning is a quality family that is established by promoting, protecting and helping to realize reproductive rights as well as providing the services, arrangements and support needed to form a family with the ideal marriageable age, regulate the number of children, the distance of children and the ideal childbearing age to regulate pregnancy and foster resilience and well-being of children. The family planning program aims to increase public awareness and participation in following family planning rules, namely through limiting the age of marriage, birth spacing, increasing family resilience, increasing family welfare, in order to realize the Small Happy and Prosperous Family Norm [1]. In an effort to launch a family planning program in Tanjungbalai City. The Office of Occupational Control and Family Planning (DPPKB) will conduct counseling on the family planning program to reduce the high birth rate. However, until now there are still many family planning consultation services carried out in several areas with low birth rates, if the location of the expansion is not always on target, it is feared that the program will not achieve its objectives. So we need a system analysis to help make decisions in site selection. One technique that can be used to determine location selection is to use a decision support system (SPK) with the Weighted Product (WP) method. For that we need a computer-based decision support system that can combine models and data to provide support to decision makers in solving problems that involve users in depth. From the above problems, the authors are interested in raising the issue and putting it into a thesis entitled "Application of the Weighted Product (WP) Algorithm for Determining Priority Locations for Family Planning Extension Program Tanjungbalai City". It is hoped that the Weighted Product method can provide convenience in determining the Priority Location of Family Planning Extension Programs to produce effective decisions and help the Department and the community